Risk of preterm birth and neonatal outcomes after cerclage placement in triplet pregnancies. (12th December 2022) - Vilchez, Gustavo; Kumar, Komal; Singh, Som; Patel, Neil; Kao, Monica; Lagos, Moraima; Duncan, Jose
Abstract: Background: The number of triplet pregnancies in the United States has increased significantly. Perinatal morbidity and mortality are higher in these pregnancies mainly due to higher preterm birth rates. Interventions to decrease the risk of preterm delivery in this population are needed. Evidence regarding cerclage placement in triplets is limited. We performed a population-based, retrospective cohort study to study the risk of preterm birth and neonatal outcomes after cerclage placement in triplet pregnancies. Methods: All U.S. triplet deliveries from 2006 to 2013 with risk factors for cervical insufficiency were selected, excluding cases with indicated preterm delivery. Cases were categorized according to cerclage placement status. The risk of preterm birth and adverse neonatal outcomes were calculated using propensity score analysis, generalized linear, and logistic regression models. Results: From ∼33 million deliveries, 43, 000 were triplets, and 7308 fulfilled eligibility criteria. There was no difference in the gestational age at delivery between the cerclage and noncerclage groups, aOR (95% CI) = 1.0(0.9–1.0). The difference between the risk of preterm delivery at <34 weeks and <32 weeks was not statistically significant. The risk of the composite outcome of neonatal complications was higher in the cerclage compared to the noncerclage group, aOR (95% CI) = 1.5 (1.1–2.2). Conclusions: Cerclage placement in triplet pregnancies does not appear to decrease preterm birth rates and seems to increase the risk of neonatal complications.